O sujeito lírico em colapso: Cecília Meireles e o fim da subjetividade na poesia - Souza, Daniel Paulo de (2014)
This thesis reflects on the nature of poetry, and also the work of Cecília Meireles, assuming that, from a phenomenological analysis that it is not possible to consider the ideas of subjectivity and lyrical subject when discussing about poetic compositions, since these notions do not represent, in fact, the poetic act, but only explain it as a rational attitude, not as a phenomenon that took place in the world. Going back to subjectivity does not mean understanding the peculiarity of this type of speech, but intends to immerse in the interiority of an "I" that does not reflect the existential movement of a new presentation of things which he performs at the moment when he is articulated in their own metaphorical significances of poetic language. Due to this, the phenomenology was chosen as a line of thought, because it suggests that there is no subject as an "absolute cogito" disconnected from the world without roots in it, but a consciousness that looks to this world with the purpose to realize it. This attitude tends to get over the relationship between "subject" and "external object" that is always taken when reading and analysis of poetic texts are the question. Merleau-Ponty, for example, investigates how the explanation of a "philosophy of subjectivity" is valid as a possible discovery that consciousness realizes itself, or simply it is a construction produced at the instant that reflection comes out and takes this consciousness as a acquisition of thought after pronouncing the "I think". Along the way, the work of Cecília Meireles is highlighted, which reveals the vivacious appearance of things, shows total admiration for the sensory spectacle offered by them and stands unique because of its look that always reveals the most unusual meanings of the world and, through a poetic speech, makes it accessible in all its visibility.